Formation of Resource Potential of Agrarian Enterprises on the Principles of Ecological and Economic Security - KHROMUSHYNA, Lyudmyla; KONIEVA, Iryna; SKRYPNYK, Yuriy; SHALYHINA, Iryna (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018, 2018)
In this article the authors have substantiated the formation of the resource potential of agrarian enterprises on the basis of compliance with the requirements of ecological and economic security. The authors define the concept of "resource potential of an agrarian enterprise" and considered the constituent structure of resource potential. The definition of "ecological and economic security of activity of agrarian enterprises" was given. It is determined that the establishment of ecological and economic security in the activities of agrarian enterprises will promote the production of organic products, will create conditions for increasing the competitiveness of enterprises. The study of the connection and interaction of elements of the resource potential of agrarian enterprises with the constituent elements of ecological and economic security was carried out. As a result of the study, the scheme of formation of resource potential of agrarian enterprises based on the requirements of ecological and economic security was proposed and grounded. The main problems, which hinder the formation of ecologically safe economic development of agrarian enterprises, and, accordingly, have a negative influence on the formation of their resource potential. The methodological basis of the study was the dialectic method of cognition and the systematic approach to the study of the problem of the formation of resource potential. In carrying out the research were applied general scientific methods: abstract-logical, monographic, generalization.